The Effect Of Financial Literacy On The Performance Of Smes Through Financial Behaviour As A Mediating Variable In Sianjur Mulamula Sub-District, Samosir Regency - Ebit Joy Daniel Sihombing; Pipit Buana Sari; Aulia Rahman Hakim Hasibuan (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine and determine the relationship between financial literacy and MSME performance through financial behavior as a mediating variable in Sianjur Mulamula District, Samosir Regency. This study uses primary data sources and collects information through questionnaire observations and quantitative models using a Likert scale and sampling 75 MSME actors as respondents The results of the study explain that: 1) financial literacy variable on MSME performance. Thus that financial literacy partially has a significant effect on MSME performance proving that financial literacy plays an important role in improving MSME performance, the results of this research hypothesis are accepted. 2) financial literacy variable on financial behavior as a mediating. Thus that financial literacy has a significant effect on financial behavior and is able to be a mediating variable, the results of this research hypothesis are accepted/supported. 3) financial behavior variable is able to mediate the performance of MSMEs. Thus, financial behavior is able to mediate and have a significant positive influence on the performance of MSMEs, the results of this research hypothesis are accepted. 4) Financial literacy variables on MSME performance through financial behavior as a mediating variable. Financial behavior is very good at mediating and has a significant influence on financial behavior on MSME performance. The results of this research hypothesis are accepted/supported.